A modular synthesis of functionalised phenols enabled by controlled boron speciation1. Issue 10 (14th March 2015) - Molloy, John J.; Law, Robert P.; Fyfe, James W. B.; Seath, Ciaran P.; Hirst, David J.; Watson, Allan J. B.
<x xml:space="preserve">Abstract</x> Functionalised biaryl phenols can be rapidly accessed via one-pot Suzuki–Miyaura cross-coupling, chemoselective control of boron solution speciation, and oxidation.